Avian I kappa B alpha is transcriptionally induced by c-Rel and v-Rel with different kinetics. - Schatzle, J D (1995)
The Rel/NF-kappa B family of transcription factors participates in the regulation of genes involved in defense responses, inflammation, healing and regeneration processes, and embryogenesis. The control of the transcriptional activation potential of the Rel/NF-kappa B proteins is mediated, in part, by their association with inhibitory proteins of the I kappa B family. This association results in the cytoplasmic retention of these factors until the cell receives a proper stimulatory signal. The I kappa B alpha gene is a target for regulation by the Rel/NF-kappa B proteins and is in fact upregulated in response to Rel/NF-kappa B activation. A naturally occurring oncogenic variant of the Rel/NF-kappa B family, v-rel, transforms avian lymphocytes, bone marrow cells, monocytes, and fibroblasts. Avian I kappa B alpha expression is upregulated in cells transformed by v-Rel. Avian I kappa B alpha is also upregulated in fibroblasts overexpressing c-Rel and oncogenic variants of c-Rel. c-Rel, a carboxy-terminally truncated variant of c-Rel, and v-Rel are all able to directly transactivate the expression of the avian I kappa B alpha gene. However, c-Rel was the most potent activator of this gene, and the induction of I kappa B alpha expression showed faster kinetics in cells overexpressing c-Rel than in those overexpressing v-Rel. The regulation of I kappa B alpha induction by the Rel proteins was shown to be dependent on a 362-bp region of the I kappa B alpha promoter that contains two potential NF-kappa B binding sites and one AP-1-like binding site. Results of electrophoretic mobility shift assays using these NF-kappa B binding sites indicate that major changes in the profile of DNA binding complexes in fibroblasts overexpressing v-Rel correlated temporally with the kinetic changes in v-Rel's ability to activate the expression of the I kappa B alpha gene.